2008
DOI: 10.1007/s00223-008-9139-0
|View full text |Cite
|
Sign up to set email alerts
|

Dried Plum Polyphenols Inhibit Osteoclastogenesis by Downregulating NFATc1 and Inflammatory Mediators

Abstract: Dried plums and their polyphenols have been shown to suppress bone resorption by downregulating receptor activator NF-kappaB ligand (RANKL). Due to the anti-inflammatory and antioxidant properties of these compounds, this study was designed to investigate whether dried plum polyphenols exert additional, more direct effects on osteoclasts and their precursors. RAW 264.7 macrophages were used as a model to study osteoclast precursors and osteoclast differentiation and activity. Under inflammatory conditions indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 53 publications
9
67
0
1
Order By: Relevance
“…The results from this in vitro experiment by Bu et al (2008) has also been confirmed in animal studies (Deyhim et al, 2005;Franklin et al, 2006;Bu et al, 2007;Smith et al, 2014a). Among these, the study by Smith et al (2014a) is slightly different in that unlike the other studies that studied longer term effects of dried plum on systemic biochemical markers of bone metabolism and alteration in gene expression as the main outcome measure, their main objective was to understand the mechanism of action by which dried plum altered bone metabolism.…”
Section: Bone Healthsupporting
confidence: 57%
“…The results from this in vitro experiment by Bu et al (2008) has also been confirmed in animal studies (Deyhim et al, 2005;Franklin et al, 2006;Bu et al, 2007;Smith et al, 2014a). Among these, the study by Smith et al (2014a) is slightly different in that unlike the other studies that studied longer term effects of dried plum on systemic biochemical markers of bone metabolism and alteration in gene expression as the main outcome measure, their main objective was to understand the mechanism of action by which dried plum altered bone metabolism.…”
Section: Bone Healthsupporting
confidence: 57%
“…Part of the rescued bone phenotype was attributed to antioxidant effects on the osteoblast since ROS, which increases in animal models after operations to induce sex hormone deficiency, has been shown to upregulate expression of RANKL [60]. Additional studies revealed that dried plum polyphenols also cause decreased osteoclast differentiation, NFATc1 expression, and bone resorption [61]. Simvastatin, a 3-hydroxy-3 methylglutaryl coenzyme A (HMG Co-A) reductase inhibitor, used to treat high cholesterol, has also been shown to function as an antioxidant that can affect bone formation and resorption.…”
Section: Therapeutic Approaches Targeting Osteoclastic Rosmentioning
confidence: 94%
“…Prunes improve the liver function (Ahmed et al, 2010b), bone health (Hooshmand and Arjmandi, 2009. ) and increase bone mass, prevents osteoporosis (Deyhim et al, 2005;Bu et al, 2008), enhances the resistance to fungal infection (El-Kereamy et al, 2011), is anticancerous (Fujii et al, 2006) and anti hypercholestremia (Tinker et al, 1991).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%